Precipitated silica, its manufacturing method, and its uses
Patent Information
- Application Number
- KR1020247017007
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-26
- Filing Date
- 2022-10-17
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2042-10-17
Smart Images

Figure 112024055257318-PCT00013_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to precipitated silica, a method for manufacturing the same, and uses the same. Background Technology
[0002] EP 1585704 discloses precipitated silica having the following physicochemical parameters:
[0003] CTAB surface area 100 - 160 m² 2 / g,
[0004] BET surface area 100 - 190 m² 2 / g,
[0005] DBP content 180 - 300 g / (100 g),
[0006] Sears Water V215 - 28 ml / (5 g),
[0007] Moisture content 4 - 8%.
[0008] These are generated at a constant AV (alkali value).
[0009] Additionally, EP 1764344 discloses precipitated silica having the following physicochemical parameters:
[0010] Relative width of pore size distribution γ 4.0 to 10.0 (g nm) / ml,
[0011] BET surface area 90 to 320 m² 2 / g,
[0012] CTAB surface area 100 to 200 m² 2 / g,
[0013] Sears water V225 to 40 ml / (5 g),
[0014] Sears Water V2 / CTAB Ratio 0.16 to 0.28 ml / (5 m 2 )
[0015] and his use in rubber mixtures.
[0016] EP 2473443 discloses a method for producing precipitated silica, comprising reacting a silicate with an acidifying agent to obtain a silica suspension, and then separating and drying the suspension, wherein the reaction between the silicate and the acidifying agent is carried out in the following manner:
[0017] (i) a step of forming an aqueous initial filler having a pH of 2 to 5,
[0018] (ii) a step of simultaneously adding silicate and an acidifying agent to the initial packing in such a manner that the pH of the reaction medium is maintained at 2 to 5,
[0019] (iii) a step of adjusting the addition of an acidifying agent while continuously adding silica to the reaction medium until the pH of the reaction medium becomes 7 to 10,
[0020] (iv) a step of simultaneously adding a silicate and an acidifying agent to the reaction medium in such a manner that the pH of the reaction medium is maintained at 7 to 10,
[0021] (v) a step of adjusting the addition of silicate while continuously adding an acidifying agent to the reaction medium until the pH of the reaction medium becomes 2.5 to 5.3,
[0022] (vi) a step of contacting the reaction medium with an acidifying agent and a silicate in such a manner that the pH of the reaction medium is maintained at 2.5 to 5.3,
[0023] (vii) a step of introducing an alkaline active ingredient, preferably a silicate, into the reaction medium to increase the pH of the reaction medium to a value of 4.7 to 6.3, wherein this step (vii) is optional when the reaction medium having a pH of 5.0 to 5.3 is brought into contact with the acidifying agent and the silicate in step (vi) so that the pH of the reaction medium is maintained at 5.0 to 5.3.
[0024] In addition, from EP 2794479 B1, a method for producing silica is known in which a silicate is reacted with at least one acid to obtain a silica suspension, and then the suspension is separated and dried by performing a reaction between the silicate and the acid according to the following sequential steps:
[0025] (i) a step of forming an aqueous initial filler having a pH of 2 to 5,
[0026] (ii) a step of simultaneously adding silicate and acid to the initial packing in such a manner that the pH of the reaction medium is maintained at 2 to 5,
[0027] (iii) a step of stopping the addition of acid and continuing to add silica to the reaction medium simultaneously until the pH of the reaction medium becomes 7 to 10,
[0028] (iv) a step of simultaneously adding silicate and acid to the reaction medium in such a manner that the pH of the reaction medium is maintained at 7 to 10,
[0029] (v) A step of stopping the addition of silicate and simultaneously continuing to add acid to the reaction medium until the pH of the reaction medium becomes less than 6,
[0030] Here, in step (ii), the acid used after achieving the gel point in the reaction medium is a concentrated acid from the group consisting of sulfuric acid with a concentration of at least 80 mass%, acetic acid or formic acid with a concentration of at least 90 mass%, nitric acid with a concentration of at least 60 mass%, phosphoric acid with a concentration of at least 75 mass%, and hydrochloric acid with a concentration of 30 mass%.
[0031] US 2017 / 0044020 A1 discloses precipitated silica having the following:
[0032] BET surface area 45 to 550 m² 2 / g,
[0033] CTAB surface area 40 to 525 m² 2 / g,
[0034] Content of polycarboxylic acid and corresponding carboxylate, expressed as total carbon content, at least 0.15 wt% (C), and
[0035] Crafting distribution range ldp greater than 0.65
[0036] EP 1764344 B1 discloses precipitated silica having the following physicochemical parameters:
[0037] Relative width of pore size distribution γ 4.0 - 10.0 (g nm) / ml,
[0038] BET surface area 90 - 320 m² 2 / g,
[0039] CTAB surface area 100 - 200 m² 2 / g,
[0040] Sears Water V225 - 40 ml / (5g),
[0041] Sears Soo V2 / CTAB Ratio 0.16 - 0.28 ml / (5 m 2 ).
[0042] A particular disadvantage of known silica is its relatively high surface area (approx. 150 m²). 2 Silica (with a specific surface area greater than 1 / g) exhibits limited dispersibility, particularly in so-called green tire mixtures, and as a result, reinforcement properties cannot be optimized in typical tire tread mixtures. This implies that the full reinforcement potential of such silica cannot be fully utilized due to the lack of optimal dispersibility. While such silica should impart very good wear resistance to the tire tread compounds reinforced with it, this is achieved only partially or incompletely.
[0043] The problem addressed by the present invention is to provide silica having advantages in dispersibility and reinforcing characteristics compared to silica known from the prior art. Accordingly, it should be possible to establish an extended life of the tire due to lower wear, i.e., optimized wear resistance, without adversely affecting other properties of the tire.
[0044] The present invention provides precipitated silica characterized by the following physicochemical parameters:
[0045] CTAB 50 m 2 / g - 450 m 2 / g, preferably 140 m 2 / g - 450 m 2 / g, more preferably 150 m 2 / g - 350 m 2 / g, particularly preferably 180 m 2 / g - 330 m 2 / g,
[0046] BET / CTAB ratio < 1.3, preferably 0.8 - 1.2, more preferably 0.9 - 1.2, particularly preferably 0.9 - 1.1,
[0047] Tailing factor 5% ≥ 150 nm, preferably 150 - 1000 nm, more preferably 170 - 500 nm, particularly preferably 175 - 400 nm.
[0048] The sears number V2 of the precipitated silica according to the present invention may be 5 - 15 ml / (1.5 g), preferably 8 - 12 ml / (1.5 g), more preferably 10 - 12 ml / (1.5 g).
[0049] The Ro-Tap value of the precipitated silica according to the present invention > 300 μm may be > 75 wt%, preferably > 80 wt%, more preferably > 85 wt%.
[0050] The precipitated silica according to the present invention may be used in a compressed form, more preferably in the form of pellets. Here, it is possible for at least 50% of the granular grains produced from the Lo-Tap > 300 μm fraction to have a maximum dimension of the granular grains (defined as "grain length") of 1.0 mm or more in terms of height, width, or length, preferably > 1.5 mm, more preferably > 2.5 mm, and particularly preferably > 3.0 mm. The grain length is measured with a Keyence VR-5200 3D profilometer.
[0051] To achieve ideal, relatively dense packing of aggregates or clusters with intrinsic stabilization, a specific ratio of relatively coarse aggregates or clusters to relatively small aggregates or clusters must be established. The denser the packing, the higher the interaction between these particles, and the more stable the packing. The proportion of coarse particles can be described through the width of the distribution function in the axial coordinate value of the particle size distribution by CPS at a height of 5%. This value is expressed as a ratio to the peak maximum of the particle size distribution, and d 95 The value is multiplied. Therefore, this tailing factor of 5% represents the desired asymmetry of the particle size distribution. This creates a stabilized intrinsic starting structure that is hardly destroyed during mixing operations, for example in rubber mixtures, even under high shear forces, and thus creates additional reinforcement of the rubber matrix. By limiting the proportion of coarse particles, dispersibility is not deteriorated to the extent that it adversely affects wear resistance.
[0052] The present invention further provides a method for manufacturing silica according to the present invention, characterized by the following:
[0053] a) a step of producing an initial charge by adding H2SO4 to water at a temperature of 60°C to 90°C until a pH of less than 4 is established,
[0054] b) a step of simultaneously adding water glass and H2SO4 to the initial packing using 3-55% of the total amount of water glass at a pH of less than 4,
[0055] c) Step of stopping the metering of H2SO4,
[0056] d) a step of continuing the metered addition of water glass until a pH of 3-9 is established, and then stopping the addition of water glass,
[0057] e) a step of applying the suspension to aging by stirring for an additional 5-90 minutes without the additional addition of H2SO4 or water glass,
[0058] f) A step of simultaneously metering and adding water glass and H2SO4 to a suspension with a pH greater than 8,
[0059] g) A step of stopping the metered addition of water glass after the entire amount of water glass has been added,
[0060] h) A step of continuing metered addition of H2SO4 until a pH of less than 5 is reached, and then stopping the addition of H2SO4,
[0061] i) A step of filtering and drying the suspension,
[0062] Here, water glass having a SiO2 content of more than 20 wt% and H2SO4 having a concentration of more than 90 wt% are used, and stirring is continuous in method steps a) to h).
[0063] It is also possible to use other acids, such as HCl or CO2, instead of H2SO4.
[0064] The present invention further provides an additional method for producing silica according to the present invention, characterized by the following:
[0065] a) a step of producing an initial filler by adding 5-50 weight% of the total amount of water glass to water at a temperature of 45℃ to 90℃,
[0066] b) a step of adding H2SO4 until the pH reaches less than 3, and then stopping the addition of H2SO4,
[0067] c) A step of applying the suspension to aging by stirring for an additional 5-90 minutes without the additional addition of H2SO4 or water glass,
[0068] d) adding water glass by weighing it until a pH of 3-9 is established, and then stopping the addition of water glass,
[0069] e) A step of applying the suspension to aging by stirring for an additional 5-90 minutes without the additional addition of H2SO4 or water glass,
[0070] f) subsequently adding 5 to 50 weight percent of the total amount of water glass, and then stopping the addition of water glass,
[0071] g) A step of applying the suspension to aging by stirring for an additional 5-90 minutes without the additional addition of H2SO4 or water glass,
[0072] h) A step of adding H2SO4 until the pH reaches less than 3, and then stopping the addition of H2SO4,
[0073] i) A step of applying the suspension to aging by stirring for an additional 5-90 minutes without the additional addition of H2SO4 or water glass,
[0074] j) A step of adding water glass up to a pH of 3 to 9, and then stopping the addition of water glass,
[0075] k) A step of applying the suspension to aging by stirring for an additional 5-90 minutes without the additional addition of H2SO4 or water glass,
[0076] l) Subsequently, a step of adding the remaining amount of water glass and then stopping the addition of water glass,
[0077] m) A step of applying the suspension to aging by stirring for an additional 5-90 minutes without the additional addition of H2SO4 or water glass,
[0078] n) a step of adding H2SO4 until the pH reaches 7.5 to 9.0, and then stopping the addition of H2SO4,
[0079] o) a step of optionally heating the suspension to 85 to 95°C,
[0080] p) A step of applying the suspension to aging by stirring for an additional 5-90 minutes without the additional addition of H2SO4 or water glass,
[0081] q) A step of adding H2SO4 until the pH reaches less than 5, and then stopping the addition of H2SO4,
[0082] r) A step of filtering and drying the suspension,
[0083] Here, water glass having a SiO2 content of more than 20 wt% and H2SO4 having a concentration of more than 90 wt% are used, and stirring is continuous in method steps a) to g).
[0084] The filtered and dried silica from method step r) can be pelletized or ground and then pelletized.
[0085] The suspension from the methodized r) can be dried in a spray dryer, for example, a spray dryer designed as a nozzle tower or a spin-flash dryer.
[0086] Water glass can have a weight modulus greater than 2.8.
[0087] It is also possible to use other acids, such as HCl or CO2, instead of H2SO4.
[0088] The present invention further provides uses of silica according to the present invention in rubber mixtures, battery separator foils, silicone rubber mixtures, pharmaceutical applications, dental applications, and cosmetic applications.
[0089] The present invention further provides uses of silica according to the present invention as a reinforcing agent, a carrier, a matting agent, and a free-flowing aid.
[0090] The present invention provides a rubber mixture characterized by further comprising at least one type of rubber and at least one type of precipitated silica according to the present invention. Specific details for implementing the invention
[0091] The rubber mixture according to the present invention may include a difunctional silane. The difunctional silane may be sulfur silane, vinyltriethoxysilane, vinyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, or methacryloyloxypropyltrimethoxysilane.
[0092] The sulfur silane may be a sulfur silane of the following chemical formula (I):
[0093] [(RO)3Si-R 3 -] n A (I)
[0094] In the above formula, R is the same or different, and is a straight-chain non-substituted or branched-chain non-substituted (C1-C 10 )-alkyl, preferably (C1-C6)-alkyl, more preferably methyl or ethyl group or alkyl polyether group -(R 1 -O) m -R 2 and, here R 1 It is identical or different, branched or unbranched, saturated or unsaturated, aliphatic, divalent C1-C 30 It is a hydrocarbon group, m is an average of 1 to 30, and R 2 is unsubstituted or substituted, branched or unbranched, 1-valent C1-C 30 -alkyl, C2-C 30 -Alkenyl, C6-C 30 -aryl or C7-C 30 - It is an aralkyl group, and R 3 It is branched or unbranched, saturated or unsaturated, aliphatic, aromatic, or mixed aliphatic / aromatic divalent C1-C 30 It is a hydrocarbon group, and A is S when n = 2. x(x = 1-10), and A is SH, SC(=O)R, or SCN when n = 1. The sulfur silane is preferably bis[3-triethoxysilyl)propyl]tetrasulfide, bis[3-triethoxysilyl)propyl]disulfide, 3-mercaptopropyltriethoxysilane, (EtO)3Si-(CH2)3-SC(O)-C7H 15 , (EtO)3Si-(CH2)3-SCN, (C 13 H 27 (OCH2CH2)5-O-)2(CH3O)Si-(CH2)3-SH or (C 13 H 27 It can be (OCH2CH2)5-O-)2(C2H5O)Si-(CH2)3-SH.
[0095] In addition to the silica according to the present invention, the rubber mixture may also contain additional fillers.
[0096] The filler usable in the rubber mixture according to the present invention comprises the following filler:
[0097] - Carbon Black: The carbon black used herein can be manufactured by a lamp black process, a furnace black process, a gas black process, or a thermal black process. Carbon black can also be obtained from recycling methods. The carbon black is 20 to 200 m 2 It can have a BET surface area of / g. Carbon black can also be optionally doped with, for example, Si.
[0098] - Amorphous silica, preferably precipitated silica or formed silica. Amorphous silica is 5 to 1000 m 2 / g, preferably 20 to 400 m 2 It can have a specific surface area (BET surface area) of 10 to 400 nm and a primary particle size of 10 to 400 nm. The silica can optionally also be in the form of a mixed oxide with other metal oxides, such as oxides of Al, Mg, Ca, Ba, Zn, and titanium.
[0099] - Synthetic silicates, e.g., aluminum silicates or alkaline earth silicates, e.g., magnesium silicates or calcium silicates. 20 to 400 m 2 Synthetic silicate having a BET surface area of / g and a primary particle diameter of 10 to 400 nm.
[0100] - Synthetic or natural aluminum oxide and hydroxide.
[0101] - Natural silicates, such as kaolin and other naturally occurring silicas.
[0102] - Glass fibers and glass-fiber products (mats, strands) or glass microbeads.
[0103] Preferably amorphous silica, more preferably precipitated silica or silicate, particularly preferably 20 to 400 m 2 It is possible to use precipitated silica having a BET surface area of 1 / g in each case in an amount of 5 to 180 parts by weight based on 100 parts of rubber.
[0104] The mentioned fillers can be used alone or as a mixture.
[0105] In a particularly preferred embodiment of the method, for the preparation of a mixture, it is possible to use 10 to 180 parts by weight of precipitated silica according to the present invention, optionally in each case with 0 to 100 parts by weight of carbon black and 0.1 to 20 parts by weight of silane based on 100 parts by weight of rubber.
[0106] Natural rubber as well as synthetic rubber is suitable for manufacturing the rubber mixture according to the present invention. Preferred synthetic rubbers are described, for example, in the literature [W. Hofmann, Kautschuktechnologie [Rubber Technology], Genter Verlag, Stuttgart 1980]. These
[0107] - Polybutadiene (BR),
[0108] - Polyisoprene (IR),
[0109] - A styrene / butadiene copolymer having a styrene content preferably 1% to 60% by weight, more preferably 2% to 50% by weight, based on the total polymer, e.g., emulsion SBR (E-SBR) or solution SBR (S-SBR),
[0110] - Chloroprene (CR),
[0111] - Isobutylene / isoprene copolymer (IIR),
[0112] - A butadiene / acrylonitrile copolymer (NBR) having an acrylonitrile content of preferably 5% to 60% by weight, preferably 10% to 50% by weight, based on the total polymer,
[0113] - Partially hydrogenated or fully hydrogenated NBR rubber (HNBR),
[0114] - Ethylene / propylene / diene copolymer (EPDM) or
[0115] - The aforementioned rubbers having additional functional groups, e.g., carboxyl, silanol, or epoxy groups, e.g., epoxidized NR, carboxyl-functionalized NBR, silanol-functionalized (-SiOH) or siloxy-functionalized (-Si-OR), amino-, epoxy-, mercapto-, hydroxyl-functionalized SBR, and mixtures of these rubbers
[0116] Includes
[0117] Of particular interest in the manufacture of automobile tire treads is anionic polymerized S-SBR rubber (solution SBR) having a glass transition temperature of -50°C or higher and a mixture of it with its diene rubber.
[0118] The rubber used may more preferably be NR or functionalized or non-functionalized S-SBR and BR.
[0119] The rubber mixture according to the present invention comprises additional rubber aids familiar to the rubber industry, such as reaction accelerators, aging stabilizers, heat stabilizers, light stabilizers, ozonation inhibitors, processing aids, plasticizers, resins, tackifiers, foaming agents, dyes, pigments, waxes, extenders, organic acids, retardants, metal oxides, and activators, such as diphenylguanidine, triethanolamine, polyethylene glycol, y I = 2-25, preferably y I = 2-15, more preferably y I = 3-10, most preferably y I = 3-6 alkoxy-terminated polyethylene glycol alkyl-O-(CH2-CH2-O) yI It may include -H, or hexanetriol.
[0120] Rubber additives may be used in familiar amounts determined by factors including the intended use. Typical amounts may be, for example, 0.1 to 50 parts by weight based on 100 parts of rubber. The crosslinking agent used may be a peroxide, sulfur, or a sulfur donor material. The rubber mixture according to the present invention may further comprise a vulcanization accelerator. Examples of suitable vulcanization accelerators may be mercaptobenzothiazole, sulfenamide, thiuram, dithiocarbamate, thiourea, and thiocarbonate. The vulcanization accelerator and sulfur may be used in amounts of 0.1 to 10 parts by weight based on 100 parts of rubber, preferably 0.1 to 5 parts by weight based on 100 parts of rubber.
[0121] The rubber mixture according to the present invention may be vulcanized at a temperature of 100°C to 200°C, preferably 120°C to 180°C, optionally at a pressure of 10 to 200 bar. Blending of the rubber, the precipitated silica according to the present invention, optional rubber additives, and silane may be performed in known mixing units, such as rollers, internal mixers, and mixing extruders.
[0122] The rubber mixture according to the present invention can be used in the manufacture of molded articles, for example, tires, particularly pneumatic tires or tire treads, cable sheaths, hoses, drive belts, conveyor belts, roller coverings, shoe soles, sealing rings, and damping elements.
[0123] The advantage of the precipitated silica according to the present invention is its dispersibility in rubber mixtures and specific reinforcing characteristics.
[0124] Analytical method for characterizing silica
[0125] Drying loss, 2 hours at 105°C - Determination of drying loss according to DIN EN ISO 787-2
[0126] Measure the weight loss of a sample heated at 105°C for 2 hours in a drying cabinet.
[0127] The procedure follows DIN EN ISO 787-2 having the specifications described below:
[0128] Remove the lid from a weighing bottle (with a flange-type lid; diameter approx. 80 mm, height approx. 30 ml) and heat it at 105°C for about 1 hour. After cooling in a desiccator, insert the lid. Determine the weight accurately to within 0.01 g on a precision balance. Accurately weigh 5–10 g of the sample (weight based on bulk density) and spread it in a uniform layer at the bottom of the weighing bottle. Carefully open the weighing bottle and heat it in a dry cabinet at (105 ± 2)°C for 2 hours (the lid is also heated, but the weighing bottle is not yet closed with it).
[0129] Carefully close the weighing bottle with the lid, cool it in a desiccator, and re-weigh it accurately to the nearest 0.01 g.
[0130] calculate
[0131] Volatile fraction / % =
[0132] E = Starting weight / g
[0133] A = Final weight / g
[0134] pH - pH of silica according to DIN EN ISO 787-9
[0135] The procedure follows DIN EN ISO 787-9 having the specifications described below:
[0136] The pelletized sample material is finely ground using a mortar and pestle and then weighed.
[0137] Prepare a 5% (m / m) aqueous suspension of the sample to be analyzed. For this purpose, demineralized (DMPA) water is used.
[0138] Before measuring pH, the sample suspension is stirred on a stirrer for at least 5 minutes.
[0139] pH is measured at 23°C on a pre-calibrated pH meter, Model 780 from Metrohm, equipped with a pH electrode 6.0228.000 (from Metrohm).
[0140] CTAB surface area - determined according to ISO 5794-1-G
[0141] The method is based on the adsorption of buffered CTAB (N-cetyl-N,N,N-trimethylammonium bromide) in an aqueous solution on the "external" surface of silica, also referred to as a "rubber-active surface." The unadsorbed CTAB is back-titrated with NDSS (dioctyl sodium sulfosuccinate solution). The endpoint of the titration is the maximum increase in the opacity of the solution.
[0142] The procedure follows ISO 5794-1 G with the specifications, additions, and starters listed below:
[0143] In the sample preparation process, specimens of silica and silicate in the form of coarse particles are preferably ultrafinely ground by a suitable mill, crushed by a mortar and pestle, sieved through a 90 μm sieve, and fractionated by a 150 μm sieve without crushing by a mortar and pestle, as described in the standard.
[0144] Test specimen and 200 m 2A suspension consisting of a CTAB solution having an estimated CTAB surface area of less than / g is stirred for 10 minutes. Test specimen and 200 m 2 A suspension consisting of a CTAB solution having an expected CTAB surface area of 1 / g or more is stirred for 35 minutes as described in the standard.
[0145] After adsorption, the silica is filtered through a 0.2 μm polyamide filter.
[0146] The filtrate is titrated using a metroprocessor equipped with an autosampler and a Tirando 809. The phototrode used is a Spectrosense 523 nm from metro.
[0147] BET surface area (N 2 , multipoint) - Measurement according to DIN ISO 9277
[0148] The method serves to determine the N2 specific surface area of silica by the BET method according to DIN ISO 9277. In this method, the measurement is determined by the low-temperature adsorption of nitrogen at a specified partial pressure. The analysis is performed as a multipoint determination, and when a total of five measurement points are determined, it exhibits substantially linear behavior in the partial pressure range (p / po) of 0.05–0.20.
[0149] The procedure follows DIN ISO 9277 having the specifications listed below:
[0150] Carefully crush the pelletized sample with a spatula before weighing, then Micromerics bagprep TM (MICROMERITICS VacPrep TM ) 061 Degas the air under reduced pressure for 60 minutes at (160 + / - 2)℃ using an exhausted degassing temperature controller.
[0151] To determine the BET surface area, record the following five relative pressure points (p / po) during the adsorption step: 0.0500; 0.0875; 0.1250; 0.1625 and 0.2000.
[0152] For measurement, the static volumetric test method and Dewar vessels and the TriStar 3000 series (3000 / 3020 / 3030) from Micromerics are used.
[0153] Raw-tap (> 300 μm) - Sieve analysis according to ISO 5794-1 Appendix F
[0154] Sieve analysis is performed using a rotary sieving machine (Tyler Ro-Tap RX-29 analytical sieving machine with a timer switch). The method is carried out according to ISO 5794-1 Appendix F. For sieve analysis, test sieves of various mesh sizes are stacked one on top of another (analytical sieve with metal mesh, ISO 3310-1, nominal mesh size 75 μm, sieve diameter 200 mm; analytical sieve with metal mesh, ISO 3310-1, nominal mesh size 150 μm, sieve diameter 200 mm; analytical sieve with metal mesh, ISO 3310-1, nominal mesh size 300 μm, sieve diameter 200 mm). The sieving towers are inserted into the analytical sieving machine in the specified order. The sieve residue is measured in the following manner: The sample is gently homogenized prior to determination. 100 g is accurately weighed to within 0.01 g on a precision balance and placed in a beaker, and the sample is quantitatively transferred onto the top sieve (300 μm). Low-tap sieving is performed with a tapper for 5 minutes. After sieving is finished, the sieving column is removed, and the fractions on the 75 μm and 300 μm sieves are weighed.
[0155] Calculation of sieve residue
[0156] Ro-tap < 75 μm (%) = AS·100% / E
[0157] and
[0158] Law-Tab > 300 μm (%) = A300·100% / E
[0159] and
[0160] Ro-Tap > 150 μm (%) = A150·100% / E
[0161] Here
[0162] A300 = Residue on a 300 μm sieve (g)
[0163] AS = Residue in the sieve (g)
[0164] E = Starting weight (g)
[0165] Tailing Factor 5% - Determination of Particle Size Distribution and Its Asymmetry by Disk Centrifuge
[0166] The particle size distribution of silica is determined. The sample to be analyzed is dispersed in an aqueous solution and separated according to its particle size in a disc centrifuge: the larger and therefore heavier the particles, the faster they move in the centrifuge's gravitational field. They pass through the light barrier inside; absorption is measured as a function of time. Using this data, the particle size distribution—that is, the frequency as a function of particle diameter—is calculated.
[0167] Note: Due to English notation, " ," is given as " ." in the description of this test method.
[0168] machinery and tools
[0169] CPS DC24000 Disc Centrifuge
[0170] Hielscher UP200S ultrasonic finger with S14 sonotrode
[0171] Cooling tank, e.g. Julabo F12
[0172] Fritsch mill; "Pulverisette 14" model with an 80 μm sieve
[0173] analytical balance
[0174] Luer Disposable Syringes: 1.0 ml and 2.0 ml
[0175] 30 ml snap-lid vial, d = 28 mm, h = 75 mm
[0176] Magnetic stirrer with a stirrer rod
[0177] chemical substances
[0178] Ethanol, pA, for example from Merck
[0179] deionized water
[0180] Sucrose, powder, >= 99.7%, e.g. from Acros
[0181] Dodecane 99%, for example from Merck
[0182] PVC reference standards, for example, from CPS Instruments
[0183] method
[0184] Preparation of a disk centrifuge
[0185] Adjust the disc centrifuge to the desired speed. For precipitated silica, set the speed to 20,000 rpm.
[0186] A running disc centrifuge is filled with a density gradient of sucrose solution and blanketed with a layer of dodecane.
[0187] Sugar solutions of different concentrations are prepared. Here, the concentrations of the sugar solutions are w = 8% to w = 24%. A density gradient is formed in 9 steps:
[0188] 24% / 22% / 20% / 18% / 16% / 14% / 12% / 10% / 8%
[0189] For each density step, inject 1.6 ml of sugar solution into a disc centrifuge, starting at the highest concentration. Alternatively, only two types of sugar solutions with the highest and lowest concentrations can be prepared and mixed together in a metering syringe at the required mixing ratio. Before injection, the syringe must be shaken briefly to mix the sugar solutions. Finally, inject 0.5 ml of dodecane.
[0190] Sample manufacturing
[0191] All precipitated silica samples (including powder samples) are ground in a Fritsch mill before crystallization. Fumed silica samples are not ground.
[0192] Here, 15 g (± 0.5 g) of sample material is ground in a fritch mill.
[0193] Weigh 0.75 g (± 0.05 g) of ground material into a 30 ml snap-lid vial, and add 15 ml of deionized water.
[0194] Secure the filled snap-lid vial to the cooling bath using a clamp. The cooling bath is pre-equilibrated to a temperature of 5°C (± 1°C). The ultrasonic finger is positioned so that, at the time of measurement, the sonotrode is immersed 5.5 cm (but at least 5 cm) deep into the vial from the upper edge of the snap-lid vial.
[0195] The sample is sonicated at 100% power and 100% pulse for 15 minutes.
[0196] procedure
[0197] Before starting the measurement, the centrifuge is heated at a preset speed for at least 30 minutes after the formation of the density gradient.
[0198] The measurement procedure to be used is invoked by the instrument software. For silica measurement, the following parameters must be established:
[0199] Sample Parameters:
[0200] Maximum diameter: 5.1 micrometers
[0201] Minimum diameter: 0.02 micrometers
[0202] Particle density: 2.0 g / ml
[0203] Particle refractive index: 1.44
[0204] Particle absorption: 0.001 K
[0205] Non-sphericity factor: 1.1
[0206] Correction Standard Parameters:
[0207] Peak diameter: xxx micrometers 1)
[0208] Half-height peak width: 0.2 micrometers 1)
[0209] Particle density: 1.385 g / ml 1)
[0210] Fluid Parameters:
[0211] Fluid density: 1.045 g / ml
[0212] Fluid refractive index: 1.344
[0213] Fluid viscosity: 1.2 cps (counts per second)
[0214] Presented parameters:
[0215] Display Mode: Weight
[0216] X-axis scale: logarithmic
[0217] 1) → Input according to the calibration standard used and the manufacturer's data.
[0218] In the "System Configuration" sub-menu, the measurement wavelength is set to 470 nm.
[0219] Sample variance is analyzed by switching to the "Operate Analyzer" sub-menu. The steps required for measurement are read sequentially from the "Command" line.
[0220] Before each measurement, the calibration standard must be recorded. The corresponding preliminary settings are performed under "Options" in the "Analyzer Operation" sub-menu.
[0221] In each case, inject 0.1 ml of standard or sample suspension. Stop the measurement via the "Stop" button when the measurement signal drops below the baseline.
[0222] For each sample to be analyzed, perform double determination (including variance).
[0223] result
[0224] The weight distribution is verified by applying Mie theory using raw data curves (absorption measurements). The following is reported:
[0225] Peak (nm) - the most common particle size corresponding to the axial coordinate value of the maximum value of the distribution function;
[0226] Half-height width (d 50 ) (nm) - corresponds to the width of the distribution function at 50% of its maximum value;
[0227] Average (weight-average) (nm) - the horizontal coordinate value in the distribution function that divides the area under the curve into two equal halves;
[0228] Median (50th weight percentile) (nm) - particle size at 50% of the cumulative curve;
[0229] d 25 (25th excess size weight percentile) (nm) - Particle size where 25% of the distribution is in excess (from the cumulative curve)
[0230] d 75 (75th excess size weight percentile) (nm) - Particle size where 75% of the distribution is in excess (from the cumulative curve)
[0231] d 95 (95th excess size weight percentile) (nm) - Particle size in which 95% of the distribution is in excess (from the cumulative curve)
[0232] Tailing factor 5%: Confirmation of asymmetry in particle size distribution from measurements by disk centrifugation.
[0233] Asymmetry is identified from the weight-based size distribution (Fig. 1). For this purpose, the peak, the width of the distribution at the 5% peak height, and d 95 The relationship between the values of is expressed as follows (Fig. 1):
[0234] Tailing factor 5% =
[0235] Sears number V 2 - Determination of Seas number in hydrophilic silica
[0236] It is possible to determine the Seas number as a measure of the number of free silanol groups by titrating silica with a standard 0.1 mol / l potassium hydroxide solution in the pH range of 4 to 9.
[0237] The determination method is based on the following chemical reaction, where ≡SiOH is presumed to represent the silanol group of silica:
[0238] ≡SiOH + NaCl → ≡SiONa + HCl
[0239] HCl + KOH → KCl + H2O.
[0240] procedure:
[0241] Approximately 10.0 g of powdered, spherical, or granular silica is uniformly crushed using a Fritsch mill (Pulvery Set 14 with an 80 μm screen) at 10,000 rpm for 60 seconds. Approximately 1.50 g of the thus treated silica is accurately weighed to the nearest 0.1 mg into a 250 ml beaker and mixed with 150 ml of NaCl solution (adjusted to pH 3 using β(NaCl) = 200 g / l and hydrochloric acid c(HCl) = 1 mol / l). After the sample is completely wetted, the suspension is dispersed using an Ultra Turrax PT1300D (from Polytron) at a speed of 20,000 rpm for 30 seconds.
[0242] Before titration, calibrate the pH meter (LL Unitrod pH electrode from Metrom, model: PT1000) at room temperature using buffer solutions (pH 4.00, pH 7.00, and pH 9.00). First, measure the starting pH of the suspension using the pH meter, and then adjust the pH to 4.00 using potassium hydroxide solution (0.1 mol / l) or hydrochloric acid solution (0.1 mol / l) depending on the result. Subsequently, perform titration to pH 9.00 using a 0.1 mol / l standard KOH solution. The consumption of KOH solution (ml) for pH 4.00 to pH 9.00 is V pH4-9 It corresponds to. In the same way, a blank titration (without the addition of silica) is performed. The blank value of the solution is the volume V of potassium hydroxide solution required to titrate the NaCl solution from pH 4 to pH 9 without silica. BL Write down.
[0243] Calculate the Seas number (unit ml / (1.5 g)) based on the original substance from the following:
[0244] Sears 원래 물질 = (V pH4-9 - V BL ) * T * (1.5 g) / E
[0245] Calculate the sears number based on dry matter (unit ml / (1.5 g)) from the following:
[0246] Sears 건조 물질 = (V pH4-9 - V BL ) * T * (1.5 g) / E * (100 / (100 - TV))
[0247] Here, T = the titer of the standard KOH solution used
[0248] E = Initial mass of the sample (g)
[0249] TV = Drying loss (%) of silica sample
[0250] Sears원래 물질 It corresponds to Sears number V2.
[0251] Examples
[0252] The pH during sedimentation is measured at 60°C unless a different temperature is specified in the experimental description.
[0253] Example 1:
[0254] First, 1474 l of water is charged into a reactor equipped with a propeller stirrer system and heated to 90°C. The initial charge is adjusted to pH 2.3 using sulfuric acid. Within 22 minutes, 220 kg of water glass (density 1.345 kg / l, 27% SiO2, 8% Na2O) and sulfuric acid (density 1.84 kg / l, 96% H2SO4) are added simultaneously to make the pH of the reaction medium 2.3. Subsequently, the metering of sulfuric acid is stopped, and the metering of water glass is continued until the pH reaches 8.1 (2.55 kg / min). The reaction medium is aged at 90°C for 15 minutes. Subsequently, 379 kg of water glass is added within 38 minutes. During this process, the metering of sulfuric acid is controlled in such a way that the pH of the reaction medium becomes 9 (measured at 23°C). Subsequently, the addition of water glass is stopped, and the supply of sulfuric acid is continued until a pH of 2.3 (measured at 23°C) is reached. The resulting suspension is filtered, typically washed with water, and subjected to a simple drying operation, such as spray-drying or spin-flash drying. Where appropriate, the powder thus obtained is pelletized.
[0255] Pelletized silica has the following analytical parameters:
[0256] Drying loss, 2 hours at 105℃ 6.3%
[0257] CTAB surface area 215 m² 2 / g
[0258] pH, 5% in water; 5.2 at 23℃
[0259] BET surface area (N2, multiple points) 235 m² 2 / g
[0260] BET - CTAB 20 m 2 / g
[0261] BET / CTAB 1.1
[0262] Tailing factor 5% 236 nm
[0263] Example 2:
[0264] First, 1676 l of water and 121 kg of water glass (density 1.345 kg / l, 27% SiO2, 8% Na2O) are charged into a reactor equipped with a propeller stirrer system and heated to 90°C. 16 kg of sulfuric acid (density 1.84 kg / l, 96% H2SO4) is added within 16.7 minutes until the pH reaches 2.5. Then, the mixture is aged for 5 minutes, and the pH is adjusted to 6 using water glass (1 kg / min). The mixture is aged at 90°C for 30 minutes. Then, 120.9 kg of water glass is metered in at a rate of 13.33 kg / min. The mixture is then aged for an additional 5 minutes. Subsequently, 16 kg of sulfuric acid is metered in at a rate of 0.95 kg / min until the pH reaches 2.5. The pH is readjusted to pH 6 using water glass (1 kg / min). Aging is performed again at the above temperature for 15 minutes. Following aging, 120.9 kg of water glass is additionally metered and added at a rate of 13.33 kg / min. Aging is then performed for an additional 5 minutes. Subsequently, 7 kg of sulfuric acid is added at a rate of 0.95 kg / min until the pH reaches 8.5. Afterward, aging is performed for 30 minutes, and additional sulfuric acid is added at a rate of 0.4 kg / min until the pH reaches 3.3 (measured at 23°C). The resulting suspension is filtered, washed with water as usual, and subjected to spin-flash drying. The powder thus obtained is subsequently pelletized. The pelletized silica has the following analytical parameters:
[0265] Drying loss, 3.8% at 105℃ for 2 hours
[0266] CTAB surface area 158 m² 2 / g
[0267] pH, 5% in water; 6.4 at 23℃
[0268] N2 surface area (N2, multipoint) 173 m 2 / g
[0269] BET - CTAB 15 m 2 / g
[0270] BET / CTAB 1.1
[0271] Tailing factor 5% 180 nm
[0272] Example 3:
[0273] First, 1700 L of water and 122.3 kg of water glass (density 1.345 kg / L, 27% SiO2, 8% Na2O) are charged into a reactor equipped with a propeller stirrer system and heated to 53°C. 16 kg of sulfuric acid (density 1.84 kg / L, 96% H2SO4) is metered at a metering rate of 1.9 kg / min until the pH reaches 2.5. Then, the mixture is aged for 5 minutes. Then, water glass is metered at a metering rate of 1 kg / min until the pH reaches 6. Then, the mixture is aged for 30 minutes. After aging, an additional 120.9 kg of water glass is added within 3.3 minutes. Then, after aging the mixture for 5 minutes, an additional 16 kg of sulfuric acid is added at a rate of 1.9 kg / min until the pH reaches 2.5. After aging for 5 minutes, the pH is adjusted to 6 using water glass (1 kg / min). Then, the mixture is aged for 15 minutes, and an additional 120.9 kg of water glass is added to the suspension. Then, the mixture is aged for 5 minutes, and then 7 kg of sulfuric acid is added at a rate of 1.9 kg / min until the pH reaches 8.5. Then, the mixture is heated to 90°C within 21 minutes and aged at that temperature for 30 minutes. Then, sulfuric acid is metered in at a rate of 0.4 kg / min until the reaction mixture reaches a pH of 4.0 (measured at 23°C).
[0274] The resulting suspension is filtered, typically washed with water, and subjected to spin-flash drying. The powder thus obtained is subsequently pelletized. The pelletized silica has the following analytical parameters:
[0275] Drying loss, 2 hours at 105℃ 4.7%
[0276] CTAB surface area 297 m² 2 / g
[0277] pH, 5% of water; 5.6 at 23℃
[0278] N2 surface area (N2, multipoint) 322 m 2 / g
[0279] BET - CTAB 25 m 2 / g
[0280] BET / CTAB 1.1
[0281] Tailing factor 5% 256 nm
[0282] Example 4:
[0283] First, 1480 l of water is charged into a reactor equipped with a propeller stirrer system and heated to 84°C. The initial charge is adjusted to pH 2.3 using sulfuric acid. Within 22 minutes, 220 kg of water glass (density 1.345 kg / l, 27% SiO2, 8% Na2O) and sulfuric acid (density 1.84 kg / l, 96% H2SO4) are added simultaneously to make the pH of the reaction medium 2.3. Subsequently, the metering of sulfuric acid is stopped, and the metering of water glass is continued until the pH reaches 4.4 (2.56 kg / min). The metering of water glass is stopped, and the pH of the suspension is raised to 6.0. The reaction medium is aged at 84°C for 15 minutes. Then, 18.7 kg of water glass is metered in at a rate of 9.8 kg / min until the pH reaches 9 (measured at 23°C). Subsequently, 350 kg of water glass is added within 35 minutes. During this process, the metering of sulfuric acid is controlled so that the pH in the reaction medium becomes 9 (measured at 23°C). Subsequently, the addition of water glass is stopped, and the supply of sulfuric acid is continued until a pH of 2.6 (measured at 23°C) is reached. The resulting suspension is filtered, typically washed with water, and subjected to a simple drying operation, such as spray-drying or spin-flash drying. If appropriate, the powder thus obtained is pelletized.
[0284] Pelletized silica has the following analytical parameters:
[0285] Drying loss, 2 hours at 105℃ 3.81%
[0286] CTAB surface area 248 m² 2 / g
[0287] pH, 5% in water; 6.4 at 23℃
[0288] N2 surface area (N2, multipoint) 272 m 2 / g
[0289] BET - CTAB 24 m 2 / g
[0290] BET / CTAB 1.1
[0291] Tailing factor 5% 260 nm
[0292] Example 5:
[0293] First, 1477 l of water is charged into a reactor equipped with a propeller stirrer system and heated to 78°C. The initial charge is adjusted to pH 2.3 using sulfuric acid. Within 22 minutes, 220 kg of water glass (density 1.345 kg / l, 27% SiO2, 8% Na2O) and sulfuric acid (density 1.84 kg / l, 96% H2SO4) are added simultaneously to make the pH of the reaction medium 2.3. Subsequently, the metering of sulfuric acid is stopped, and the metering of water glass is continued until the pH reaches 4.3 (2.56 kg / min). The metering of water glass is stopped, and the pH of the suspension is raised to 6.0. The reaction medium is aged at 78°C for 15 minutes. Next, 27.3 kg of water glass is metered in at a rate of 10.1 kg / min to achieve a pH of 9 (measured at 23°C). Subsequently, 350 kg of water glass is added within 35 minutes. During this process, the metered addition of sulfuric acid is controlled in such a way that the pH in the reaction medium becomes 9 (measured at 23°C). Subsequently, the addition of water glass is stopped, and the supply of sulfuric acid is continued until a pH of 2.7 (measured at 23°C) is reached. The resulting suspension is filtered, typically washed with water, and subjected to a simple drying process, such as spray-drying or spin-flash drying. Where appropriate, the powder thus obtained is pelletized.
[0294] Pelletized silica has the following analytical parameters:
[0295] Drying loss, 2 hours at 105℃ 4.4%
[0296] CTAB surface area 266 m² 2 / g
[0297] pH, 5% of water; 6.3 at 23℃
[0298] N2 surface area (N2, multipoint) 303 m 2 / g
[0299] BET - CTAB 37 m 2 / g
[0300] BET / CTAB 1.1
[0301] Tailing factor 5% 239 nm
[0302] Example 6:
[0303] First, 1439 l of water is charged into a reactor equipped with a propeller stirrer system and heated to 84°C. The initial charge is adjusted to pH 2.9 using sulfuric acid. Within 22 minutes, 220 kg of water glass (density 1.345 kg / l, 27% SiO2, 8% Na2O) and sulfuric acid (density 1.84 kg / l, 96% H2SO4) are added simultaneously to make the pH of the reaction medium 2.9. Subsequently, the metering of sulfuric acid is stopped, and the metering of water glass is continued until the pH reaches 4.5 (2.43 kg / min). The metering of water glass is stopped, and the pH of the suspension is raised to 6.0. The reaction medium is aged at 84°C and pH 6 for 15 minutes. Next, 49.9 kg of water glass is metered in within 5 minutes to achieve a pH of 9.5 (measured at 23°C). Subsequently, 350 kg of water glass is added within 35 minutes. During this process, the metered addition of sulfuric acid is controlled in such a way that the pH of the reaction medium becomes 8.6. Subsequently, the addition of water glass is stopped, and the supply of sulfuric acid is continued until a pH of 2.5 (measured at room temperature) is reached. The resulting suspension is filtered, typically washed with water, and subjected to a simple drying process, such as spray-drying or spin-flash drying. Where appropriate, the powder thus obtained is pelletized.
[0304] Pelletized silica has the following analytical parameters:
[0305] Drying loss, 2 hours at 105℃ 4.5%
[0306] CTAB surface area 243 m² 2 / g
[0307] pH, 5% in water; 6.4 at 23℃
[0308] N2 surface area (N2, multipoint) 272 m 2 / g
[0309] BET - CTAB 28 m 2 / g
[0310] BET / CTAB 1.1
[0311] Tailing factor 5% 277 nm
[0312] Example 7:
[0313] First, 1446 l of water is charged into a reactor equipped with a propeller stirrer system and heated to 78°C. The initial charge is adjusted to pH 2.9 using sulfuric acid. Within 22 minutes, 220 kg of water glass (density 1.345 kg / l, 27% SiO2, 8% Na2O) and sulfuric acid (density 1.84 kg / l, 96% H2SO4) are added simultaneously to make the pH of the reaction medium 2.9. Subsequently, the metering of sulfuric acid is stopped, and the metering of water glass is continued until the pH reaches 4.7 (2.35 kg / min). The metering of water glass is stopped, and the pH of the suspension is raised to 6.0. The reaction medium is aged at 78°C and pH 6 for 15 minutes. Next, 50.1 kg of water glass is metered in within 5 minutes to achieve a pH of 9.5 (measured at 23°C). Then, 350 kg of water glass is added within 35 minutes. During this process, the metered addition of sulfuric acid is controlled so that the pH in the reaction medium becomes 8.6. Subsequently, the addition of water glass is stopped, and the supply of sulfuric acid is continued until a pH of 2.6 (measured at 23°C) is reached. The resulting suspension is filtered, typically washed with water, and subjected to a simple drying process, such as spray-drying or spin-flash drying. Where appropriate, the powder thus obtained is pelletized.
[0314] Pelletized silica has the following analytical parameters:
[0315] Drying loss, 2 hours at 105℃ 4.4%
[0316] CTAB surface area 263 m² 2 / g
[0317] pH, 5% in water; 6.2 at 23℃
[0318] N2 surface area (N2, multipoint) 297 m 2 / g
[0319] BET - CTAB 34 m 2 / g
[0320] BET / CTAB 1.1
[0321] Tailing factor 5% 360 nm
[0322] Example 8:
[0323] First, 1280 l of water is charged into a reactor equipped with a propeller stirrer system and heated to 90°C. The initial charge is adjusted to pH 2.9 using sulfuric acid. Within 22 minutes, 220 kg of water glass (density 1.345 kg / l, 27% SiO2, 8% Na2O) and sulfuric acid (density 1.84 kg / l, 96% H2SO4) are added simultaneously to make the pH of the reaction medium 2.9. Subsequently, the metering of sulfuric acid is stopped, and the metering of water glass is continued until the pH reaches 8.1 (2.45 kg / min). The metering of water glass is stopped, and the reaction medium is aged at 90°C for 15 minutes. Then, 190 kg of water glass is metered in at a rate of 10.1 kg / min within 19 minutes. Subsequently, 350 kg of water glass is added within 35 minutes. Subsequently, sulfuric acid is metered in at a rate of 1.28 kg / min to lower the pH to 2.7 (measured at 23°C). The resulting suspension is filtered, typically washed with water, and subjected to a simple drying process, such as spray-drying or spin-flash drying. Where appropriate, the powder thus obtained is pelletized.
[0324] Pelletized silica has the following analytical parameters:
[0325] Drying loss, 2 hours at 105℃ 4.5%
[0326] CTAB surface area 190 m² 2 / g
[0327] pH, 5% in water; 6.4 at 23℃
[0328] N2 surface area (N2, multipoint) 225 m 2 / g
[0329] BET - CTAB 35 m 2 / g
[0330] BET / CTAB 1.2
[0331] Tailing factor 5% 269 nm
[0332] Comparative Example 1:
[0333] In the case of Comparative Example 1, Zeosil from Solvay SA ® Uses HRS 1200 MP.
[0334] Comparative Example 2:
[0335] In the case of Comparative Example 2, Zeosil from Solvay S.A. ® Uses Premium 200 MP.
[0336] Comparative Example 3:
[0337] Comparative Example 3 is a rework of Example 2 from EP 2794479.
[0338] Comparative Example 4:
[0339] In the case of Comparative Example 4, Zeosil from Solvay S.A. ® It uses 1165 MP.
[0340] Example 9: Inspection of rubber characteristics
[0341] The terms "unvulcanized rubber mixture" and "vulcanized rubber mixture" are used as synonyms herein. Table 1 specifies the rubber chemicals used.
[0342] Table 1: Overview of Rubber Chemicals Used
[0343]
[0344] 1 Buna ® VSL 4526-2 HM is a solution styrene-butadiene rubber augmented with 37.5 phr TDAE oil; Mooney (1+4 at 100°C): 62 ME; Vinyl: 44.5%; Styrene: 26%
[0345] 2 Buna CB 24 is neodymium butadiene rubber, no oil content; cis 1,4 content: at least 96%
[0346] The silica used in the rubber mixture and its analytical values are compared in Table 2.
[0347] Table 2: Analysis Values
[0348]
[0349] The formulation used for the rubber mixture is specified in Table 3. Here, the unit "phr" ("parts per hundred rubber") refers to parts by weight based on 100 parts of the raw rubber used.
[0350] Table 3: Formulation of rubber mixtures
[0351]
[0352]
[0353] The required amount of silane to utilize the reinforcing potential of each silica was determined by the rule of three. The higher the specific surface area (the CTAB surface area is critical for rubber-related reinforcing action), the higher the amount of silane required. The base used was 160 m² 2 It is assumed that the CTAB surface area of / g requires 5.8 phr Si 266.
[0354] General methods for manufacturing rubber mixtures and their vulcanized products are described in the literature ["Rubber Technology Handbook", W. Hofmann, Hanser Verlag 1994]. Specifically, the equipment used to manufacture the rubber mixture according to the present invention, the mixing method used, and the reference mixture are shown in Table 4.
[0355] To prepare for the mixing operation, the plasticizer to be introduced is weighed in a low-melting point LDPE pouch that may be included in the treatment. In this regard, the term "plasticizer" refers to TDAE (treated distilled aromatic extract ( T reated D istilled A romatic E It is used as a synonym for extract.
[0356] Table 4: Mixing Method
[0357]
[0358]
[0359] The test specimens and sheets are vulcanized at a temperature of 165°C in a typical vulcanization press with a holding pressure of 130 bar. The vulcanization time of the mixture is 20 minutes.
[0360] The rubber test is performed according to the test method specified in Table 5.
[0361] Table 5: Test Method
[0362]
[0363] The results of the rubber test are shown in Table 6.
[0364] Table 6: Rubber-related results
[0365]
[0366] The silica according to the present invention has been found to achieve superior dispersion compared to the prior art. This also produces excellent reinforcing characteristics reflected in the reinforcing index. The higher this index, the better the utilization of the reinforcing potential of each silica.
[0367] Example 10: Inspection of rubber characteristics
[0368] In the additional mixing series, Comparative Example 4 and Example 2 of the present invention are compared. For this purpose, they are mixed according to the mixing method of Table 4 and tested according to the test method described in Table 5. The formulations are shown in Table 7.
[0369] The test specimens and sheets are vulcanized at a temperature of 165°C in a typical vulcanization press with a holding pressure of 130 bar. The vulcanization time of the mixture is 15 minutes.
[0370] Table 7: Formulation of rubber mixtures
[0371]
[0372] Table 6: Rubber-related results for Example 10
[0373]
[0374] Example 10 also demonstrates that the silica according to the present invention from Example 2 can achieve superior dispersion compared to the prior art. This also produces excellent reinforcement characteristics reflected in the reinforcement index. The higher this index, the better the utilization of the reinforcement potential of each silica.
Claims
Claim 1 Precipitated silica characterized by the following physicochemical parameters: CTAB 150 m 2 / g - 350 m 2 / g, BET / CTAB ratio < 1.3, tailing factor 5% ≥ 150 nm. Claim 2 Precipitated silica according to claim 1, characterized in that the BET / CTAB ratio is 0.9-1.
2. Claim 3 Precipitated silica according to claim 1, characterized in that the tailing factor 5% is 175-400 nm. Claim 4 Precipitated silica according to claim 1, characterized in that the BET / CTAB ratio is 0.9-1.2 and the tailing factor 5% is 175-400 nm. Claim 5 A method for manufacturing silica according to claim 1, characterized by the following: a) a step of producing an initial filler by adding H2SO4 to water at a temperature of 60°C to 90°C until a pH of less than 4 is established; b) a step of simultaneously adding water glass and H2SO4 to the initial filler at a pH of less than 4 using 3-55% of the total amount of water glass; c) a step of stopping the metering addition of H2SO4; d) a step of continuing the metering addition of water glass until a pH of 3-9 is established, and then stopping the addition of water glass; e) a step of applying the suspension to aging by stirring for an additional 5-90 minutes without further addition of H2SO4 or water glass; f) a step of simultaneously metering water glass and H2SO4 to a pH of the suspension greater than 8; g) a step of stopping the metering addition of water glass after the entire amount of water glass has been added; h) a step of continuing the metering addition of H2SO4 until a pH of less than 5 is reached, and then stopping the addition of H2SO4; i) A step of filtering and drying the suspension, wherein water glass having a SiO2 content of more than 20 wt% and H2SO4 having a concentration of more than 90 wt% are used, and stirring is continuous in method steps a) to h). Claim 6 A method for manufacturing silica according to claim 1, characterized by the following: a) a step of producing an initial packing by adding 5-50 weight% of the total amount of water glass to water at a temperature of 45°C to 90°C; b) a step of adding H2SO4 until a pH of less than 3 is reached, and then stopping the addition of H2SO4; c) a step of applying the suspension to aging by stirring for an additional 5-90 minutes without further addition of H2SO4 or water glass; d) a step of metering water glass until a pH of 3-9 is established, and then stopping the addition of water glass; e) a step of applying the suspension to aging by stirring for an additional 5-90 minutes without further addition of H2SO4 or water glass; f) a step of subsequently adding 5-50 weight% of the total amount of water glass and then stopping the addition of water glass; g) a step of applying the suspension to aging by stirring for an additional 5-90 minutes without further addition of H2SO4 or water glass; h) H2SO4 3 A step of adding until a pH below 9 is reached, and then stopping the addition of H2SO4; i) a step of applying the suspension to aging by stirring for an additional 5-90 minutes without further addition of H2SO4 or water glass; j) a step of metering water glass until a pH of 3-9 is reached, and then stopping the addition of water glass; k) a step of applying the suspension to aging by stirring for an additional 5-90 minutes without further addition of H2SO4 or water glass; l) a step of subsequently adding 5-50% by weight of the total amount of water glass, and then stopping the addition of water glass; m) a step of applying the suspension to aging by stirring for an additional 5-90 minutes without further addition of H2SO4 or water glass; n) adding H2SO4 in an amount of 7.5 to 9.o) adding until the pH reaches 0, and then stopping the addition of H2SO4; p) heating the suspension to 85 to 95°C as desired; q) applying the suspension to aging by stirring for an additional 5 to 90 minutes without further addition of H2SO4 or water glass; r) adding H2SO4 until the pH reaches less than 5, and then stopping the addition of H2SO4; r) filtering and drying the suspension, wherein water glass having a SiO2 content of more than 20 wt% and H2SO4 having a concentration of more than 90 wt% are used, and stirring is continuous in method steps a) to g). Claim 7 In paragraph 1, precipitated silica for use in rubber mixtures, battery separator foils, silicone rubber mixtures, pharmaceutical applications, dental applications, or cosmetic applications. Claim 8 Precipitated silica for use as a reinforcing agent, carrier, matting agent, or free-flow aid in claim 1. Claim 9 A rubber mixture characterized by comprising at least one type of rubber and at least one type of precipitated silica according to claim 1. Claim 10 delete
Citation Information
Patent Citations
Precipitated silica and method for producing the same
KR1020200002898A
Precipitated silica with improved processing properties
KR1020210029777A
Highly dispersible precipitated silica
KR1020050029286A
Specially precipitated silicic acids for rubberapplications
KR1020050097951A
Novel method for preparing precipitated silica
KR1020120041236A
